PENGGUNAAN MEDIA BERBAHAN ALAM KHUSUSNYA DAUN KERING UNTUK MENGEMBANGKAN MOTORIK HALUS PADA ANAK USIA DINI DI TK RUMAH BACA BU ITA - Abim Shoheri; Jenny Sukma Kasturi; Khoirotul Faradila Zahara; Nabilla Olivia Ardana; Zhafira Aulia Ramadhani; Naya Yurika Amanda; Riski Surya Amanda; Windah Sherly Utami (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the use of natural materials, particularly dried leaves, in developing fine motor skills in early childhood at TK Rumah Baca Bu Ita. This research employed a qualitative approach with a descriptive method through observation techniques. The subjects of this study were children involved in learning activities using dried leaves, such as sticking, cutting, arranging, and creating collages. The results showed that the use of dried leaves as a learning medium increased children's active participation, improved hand-eye coordination, and enhanced fine motor skills, accuracy, and patience. In addition, these activities provided concrete, enjoyable, and meaningful learning experiences by utilizing materials from the surrounding environment. Therefore, dried leaves can be used as a creative, innovative, and effective alternative learning medium to stimulate fine motor development in early childhood.